00 upvotes00 downvotes

2 views6 pagesForce on Elevator

Sep 10, 2018

Fec

© © All Rights Reserved

PDF, TXT or read online from Scribd

Force on Elevator

© All Rights Reserved

2 views

00 upvotes00 downvotes

Fec

Force on Elevator

© All Rights Reserved

You are on page 1of 6

Finding the Force on an Elevator Cable when:

I. The elevator is at rest

II. The elevator accelerates upward from rest

III. The elevator accelerates downward from rest

IV. The elevator is moving at a constant velocity

V. The elevator is moving upward and comes to rest

VI. The elevator is moving downward and comes to rest

There are 2 approaches for solving this problem using forces:

Method I Determine the sign of the acceleration and incorporate it into the force and kinematic equations

Method II Assume the acceleration is positive in F = ma for all cases and then let its sign be determined from the kinematic equations based on the information given in the problem

Method I

F (T) |
+ |
||||

m = 800 kg |
|||||

coordinate |
|||||

system |

Whenever a force is directed along a linear object such as a cable, string…it is typically referred to as the Tension (force), T.

I. The elevator is at rest

The forces acting on the elevator can be represented by:

+

T

v o = 0 m/s

v = 0 m/s

a = 0 m/s 2

W

∑ F = 0

T – mg = 0

T = mg

= (800 kg)(9.8 m/s ^{2} ) = 7840 N

II.

The elevator accelerates upward from rest

motion

v _{o} = 0 m/s

v = 10 m/s after moving 25 m

∑ F = ma

T – mg = ma

(note: ma is positive since a is in the + direction) T = m(g + a)

* Need value of a:

Given |
Needed |
||

v |
v |
∆x |
a |

v

2

= v

o

2

+

2 a∆x

Solving for a:

a =

2

v

(10

m

s

)

2

=

2

a = 2 m/s ^{2}

∆ x

2(25

m)

Therefore,

T = m(g + a) = (800 kg)(9.8 m/s ^{2} + 2 m/s ^{2} ) = 9440 N

III. The elevator accelerates downward from rest

motion

v _{o} = 0 m/s

v = 10 m/s after moving 25 m

∑ F = ma

T – mg = – ma

(note: ma is negative since a is in the – direction) T = m(g – a)

* Need value of a:

Given |
Needed |
||

v |
v |
∆x |
a |

Solving for a:

−

2

v

− (10

m

s

)

2

a =

=

2

a = 2 m/s ^{2}

∆ x

2(

−

25

m)

2

v

= v

o

2

−

2

a∆x

(noting that a < 0)

(note: ∆x < 0 since motion is in the – direction)

Therefore,

T = m(g – a) = (800 kg)(9.8 m/s ^{2} – 2 m/s ^{2} ) = 6240 N

IV. The elevator is moving at a constant velocity

motion

v _{o} = 10 m/s = constant

a = 0 m/s ^{2}

∑ F = 0

T – mg = 0

T = mg = (800 kg)(9.8 m/s ^{2} ) = 7840 N

(same as if the elevator was at rest!)

** Would the result be different if the direction of motion were reversed?

No!

V. The elevator is moving upward and comes to rest

motion

v _{o} = 10 m/s v = 0 m/s after moving 25 m

∑

F = ma

T – mg = – ma

(note: ma is negative since a is in the – direction) T = m(g – a)

* Need value of a:

2

Use

2

v

= v

o

2

−

a∆x

(noting that a < 0)

Solving for a:

v

o

2

(10

m

s

)

2

a =

=

2

a = 2 m/s ^{2}

∆ x

2(25

m)

Therefore,

T = m(g – a) = (800 kg)(9.8 m/s ^{2} – 2 m/s ^{2} ) = 6240 N

VI. The elevator is moving downward and comes to rest

motion

v _{o} = 10 m/s v = 0 m/s after moving 25 m

∑

F = ma

T – mg = ma

(note: ma is positive since a is in the + direction) T = m(g + a)

* Need value of a:

Use

v

2

= v

o

2

+

2 a∆x

(noting that a > 0)

Solving for a:

−

v

o

2

− (10

m

s

)

2

a =

=

2

a = 2 m/s ^{2}

∆ x

2(

−

25

m )

(note: ∆x < 0 since motion is in the – direction)

Therefore,

T = m(g + a)

= (800 kg)(9.8 m/s ^{2} + 2 m/s ^{2} ) = 9440 N

Method II

m = 800 kg

F (T)

_{+}

For all cases, let the forces representing the system be given by:

+

a

∑ F = ma

T

W

T – mg = ma

(note: ma is positive since a is in the + direction) T = m(g + a)

* Need value of a:

I. The elevator is at rest

a = 0 m/s ^{2}

T = mg = (800 kg)(9.8 m/s ^{2} ) = 7840 N

II. The elevator accelerates upward from rest

Given |
Needed |
||

v |
v |
∆x |
a |

Solving for a:

a =

2

v

(10

m

s

)

2

=

2

a = 2 m/s ^{2}

∆ x

2(25

m)

v

2

= v

o

2

+

2 a∆x

Therefore,

T = m(g + a) = (800 kg)(9.8 m/s ^{2} + 2 m/s ^{2} ) = 9440 N

III.

The elevator accelerates downward from rest

Using

a =

2

v

2

v

= v

=

o

2

+

(10

2

m

s

a∆x

)

2

2 ∆

x

2(

−

25

m)

a = – 2 m/s ^{2}

(note: ∆x < 0 since motion is in the – direction)

Therefore,

T = m(g + a)

= (800 kg)(9.8 m/s ^{2} – 2 m/s ^{2} ) = 6240 N

IV. The elevator is moving at a constant velocity

a = 0 m/s ^{2}

(regardless of direction)

T = mg = (800 kg)(9.8 m/s ^{2} ) = 7840 N

V. The elevator is moving upward and comes to rest

Using v

2

= v

o

2

+

2

a∆x

a =

−

v

o

2

− (10

m

s

)

2

=

2

∆ x

2(25

m)

a = – 2 m/s ^{2}

Therefore,

T = m(g + a)

= (800 kg)(9.8 m/s ^{2} – 2 m/s ^{2} ) = 6240 N

VI. The elevator is moving downward and comes to rest

Using v

2

= v

o

2

+

2

a∆x

a =

−

v

o

2

− (10

m

s

)

2

=

2

a = 2 m/s ^{2}

∆ x

2(

−

25

m )

(note: ∆x < 0 since motion is in the – direction)

Therefore,

T = m(g + a)

= (800 kg)(9.8 m/s ^{2} + 2 m/s ^{2} ) = 9440 N

## Much more than documents.

Discover everything Scribd has to offer, including books and audiobooks from major publishers.

Cancel anytime.